The Effect of Make A Match Cooperative Learning Model on Mathematics Problem Solving Ability in Elementary School - Hasni, Putri; Amelia, Chairunnisa (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The aim of this research is to determine the influence and effectiveness of the make a match cooperative learning model on students' mathematical problem solving abilities. This quantitative research focuses on Class II children at SD Negeri 064965 Medan. The technique used is quasi-experiment. Data were analyzed using Descriptive Statistics and Independent Samples T-Test to compare problem solving abilities between classes that used the Make-a-Match model and those that did not. Testing was carried out with a predetermined significance of 0.05. Interviews, evaluations, and recording are techniques used to collect data. This research compares the results of the control and experimental groups using parametric statistical tests, especially the t test. After conducting a pretest and posttest on the experimental and control groups, it was discovered that the experimental class achieved much better problem solving learning outcomes (91.25 out of 100) compared to the control class (85 out of 100). The experimental class proved that the make-a-match technique was successful in igniting students' curiosity and encouraging them to be involved in learning. The results of this research show that the Make a Match approach is a powerful enthusiasm booster for students, which ultimately increases their interest and ability to remember lesson content. The Make a Match model promises as an alternative approach in education, it can improve student learning outcomes through a positive classroom environment and a high emphasis on group scores.